The Portrayal of Megan’s Movement from Female Masculinity to Feminine in the Barely Lethal - Amin, Alfan; Handayani, Tuty (Fakultas Adab dan Humaniora, Universitas Islam Negeri Syarif Hidayatullah Jakarta, 2023)
This research describes how female masculinity portrayed Megan as the main character in the Barely Lethal movie, and then shows how Megan can change her personality from female masculine to feminine. This study uses a qualitative method with a descriptive approach by applying Judith Halberstam's theory of female masculinity as the main topic of this research. The research found that the appearance, gestures, dialogue, and culture in the data analyzed related to the concept of female masculinity. The results show that Megan is revealed to follow the concept of female masculinity, which consists of butch realness, femme pretender, male mimicry, fag drag, and naturalized masculinity. Megan is not only the protagonist, the character that dominates masculinity, but she is also the strong female, the fighter, the offensive, and also has strength that shows Megan's masculinity. Interestingly, the research also found that, as time goes by, Megan tries to change her traits from masculine to feminine, which can be seen when she likes the opposite sex, makes friends with the same sex and age friends in school, and reads mean girl book, which is typical reading for teenage girls in her environment. These portrayals conclude that someone's trait can be gradually interchangeable when triggered by outside or within themselves.